POLA KOMUNIKASI SUKU BATAK DENGAN SUKU REJANG DALAM MENJALIN KEHARMONISAN ANTAR WARGA DI DESA DUSUN CURUP KECAMATAN AIR BESI KABUPATEN BENGKULU UTARA - Linda Astuti; Vethy Octaviani; Khairil Khairil (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
Society basically consists of various cultural backgrounds, these differences tend to be prone to conflict. This requires efforts to minimize the emergence of these conflicts by maintaining relationships in the community through communication, thereby strengthening social interaction in society and will later become a forum for forming harmony. Dusun Curup Village is an area inhabited by one of two different cultures, where each group is able to maintain harmony in daily life. The two cultures are the original ethnic group, namely the Rejang Tribe and the immigrant ethnic group, namely the Batak tribe. The theoretical basis in this study is accommodation communication theory and uses communication patterns consisting of primary, secondary, linear and circular. This research was conducted using descriptive research methods using a qualitative approach. The data collection techniques in this study used two ways, namely primary data collection techniques with interview and observation techniques while secondary data collection techniques with supporting documents and literature, in addition to Miles and Huberman data analysis techniques and data validity tests, namely triangulation.The results of the study explain that in the community of the two different ethnicities, forming a circular communication pattern in communicating, the formation of this pattern is seen from the majority of daily activities which are more dominant in circular, the interaction that takes place is Dusun/bese coul language. This can be seen based on the approach using specific convergence, divergence, and maintenance, in addition to that, the real forms of harmony that exist are (1) Social aspects, which are formed from social order that is carried out in collaboration, one of which is negligent and sluggish. (2) The cultural aspect, which is manifested through an attitude of openness through mixed marriages so that each ethnic group can mingle and understand each other.